1989
DOI: 10.1007/bf01808284
|View full text |Cite
|
Sign up to set email alerts
|

Thermal synthesis and hydrolysis of polyglyceric acid

Abstract: Polyglyceric acid was synthesized by thermal condensation of glyceric acid at 80 degrees in the presence and absence of two mole percent of sulfuric acid catalyst. The acid catalyst accelerated the polymerization over 100-fold and made possible the synthesis of insoluble polymers of both L- and DL-glyceric acid by heating for less than 1 day. Racemization of L-glyceric acid yielded less than 1% D-glyceric acid in condensations carried out at 80 degrees C with catalyst for 1 day and without catalyst for 12 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
(28 reference statements)
0
28
0
Order By: Relevance
“…Although the ester bond is less stable than the amide bond, its formation is thermodynamically favorable (unlike the amide bond), and it does not form the cyclic dimer trap associated with amino acids. Polyester oligomers were formed from unactivated monomers in a drying reaction [105] and more recently in a cyclic hydration/dehydration environment [35].…”
Section: Polymersmentioning
confidence: 99%
“…Although the ester bond is less stable than the amide bond, its formation is thermodynamically favorable (unlike the amide bond), and it does not form the cyclic dimer trap associated with amino acids. Polyester oligomers were formed from unactivated monomers in a drying reaction [105] and more recently in a cyclic hydration/dehydration environment [35].…”
Section: Polymersmentioning
confidence: 99%
“…While the Fischer esterification mechanism involves an acid catalyzed rate limiting step, the hydroxyacids themselves can be a source of the acid catalyst. Specifically, there are reports in the literature of oligoester formation occuring for solutions of lactic (Filachione and Fisher, 1944;Vu et al, 2005;Espartero et al, 1996) and glyceric acid (Weber, 1989). However, this literature indicates that hydroxyacids can form significant quantities of oligoesters only under low water content conditions, and that the kinetics of the reactions can be very slow without added mineral acid catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…However, this literature indicates that hydroxyacids can form significant quantities of oligoesters only under low water content conditions, and that the kinetics of the reactions can be very slow without added mineral acid catalysts. For example, studies of oligoester formation from glyceric acid (Weber, 1989) and lactic acid (Vu et al, 2005) used continuous direct removal of water (by evaporation and refluxing, respectively) in order to favorably shift the equilibrium towards oligoesters. While formal kinetics studies of oligoester formation from hydroxyacids seem to be absent from the literature, a report of oligoester formation from lactic acid indicated that establishment of equilibrium required 100 days at room temperature (Filachione and Fisher, 1944).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the thermodynamic properties of reactions involving organic compounds are typically strongly temperature dependent, and increased temperatures may favor one set of reaction products over another. Often these two applications of thermal energy are employed simultaneously, as in the use of heat to drive polymerization reactions through dehydration (Schwartz et a1., 1975;Schwartz and Chittenden, 1976;Ivanov and Slavcheva, 1977;Epps et al, 1978;Lahav et a1., 1978;Lawless and Levi, 1979;Lahav and White, 1980;Hawker and Or6, 1981a,b;Rishpon et al, 1982;Rao et al, 1982;Weber, 1989; among others, see below). Dehydration reactions also proceed in aqueous solution, and it has been shown that those which lead to peptide bonds are energetically more favorable at elevated temperatures than they are at 25·C and 1 bar (Flegmann and Tattersall, 1979;Shock, 1992a).…”
Section: Heat As An Energy Source For the Abiotic Synthesis Of Organimentioning
confidence: 94%